Multi-application Smart Cards Technology and Applications - Hendry, Mike (Cambridge University Press, 2013)
In this book, Mike Hendry takes care to address not only smart-card technology, but the transformation of the industry as described above. His work adds to the industry’s rich body of knowledge and provides a fair and balanced view of smart cards as they exist today. This industry, however, like many industries, is in a constant state of change and evolution. As such, any book on smart cards (or any non-fiction book for that matter) will become historical in context. So, I encourage you to study the information in this book as a ‘first step’ in your journey to understand the technology and the industry. The next step – and on an on-going basis – will be to immerse yourself in the ebb and flow of the industry itself, through participation in industry associations, attendance at trade shows and events and by reading the periodicals and future new releases of books that cater to this subject